2002
DOI: 10.4049/jimmunol.169.10.5912
|View full text |Cite
|
Sign up to set email alerts
|

Selective Eosinophil Adhesion to Fibroblast Via IFN-γ-Induced Galectin-9

Abstract: Among galectin family members, galectin-9 was first described as a potent eosinophil chemoattractant derived from Ag-stimulated T cells. In the present study a role of galectin-9 in the interaction between eosinophils and fibroblasts was investigated using a human lung fibroblast cell line, HFL-1. RT-PCR, real-time PCR, and Western blot analyses revealed that both galectin-9 mRNA and protein in HFL-1 cells were up-regulated by IFN-γ stimulation. On the one hand, IL-4, known as a Th2 cytokine, did not affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 42 publications
(31 reference statements)
2
86
1
1
Order By: Relevance
“…These results are reasonable because Gal-9 expression in endothelial cells and fibroblasts can be up-regulated by interferon-␥ (IFN␥) (31,32), and the levels of IFN␥ are usually higher in RA ST than in OA ST (33). The fact that approximately one-third of vimentin-positive cells (probably synovial fibroblasts) had immunoreactive Gal-9 in the cytoplasm (Figure 2) is consistent with our finding that RA ST had 31.8% Gal-9-positive cells (Figure 3).…”
Section: Discussionmentioning
confidence: 75%
“…These results are reasonable because Gal-9 expression in endothelial cells and fibroblasts can be up-regulated by interferon-␥ (IFN␥) (31,32), and the levels of IFN␥ are usually higher in RA ST than in OA ST (33). The fact that approximately one-third of vimentin-positive cells (probably synovial fibroblasts) had immunoreactive Gal-9 in the cytoplasm (Figure 2) is consistent with our finding that RA ST had 31.8% Gal-9-positive cells (Figure 3).…”
Section: Discussionmentioning
confidence: 75%
“…In the case of galectin-9, our data suggest that galectin-9 acts as a L. major-specific tagging protein or an adhesion molecule so that macrophages can recognize L. major more efficiently. It has been known that some galectins, which can cross-link different cells expressing their oligosaccharide ligands (28,34,35), act as adhesion molecules even though galectins are soluble proteins (32,63,64). Galectin-9 contains two CRDs linked by a peptide linker and is thus intrinsically divalent (33,46,65).…”
Section: Discussionmentioning
confidence: 99%
“…is a member of them, and it was first identified as an eosinophil chemoattractant and activation factor (Matsumoto et al, 1998;Matsushita et al, 2000; Zhao-Yang Zhang 1,2 , Jia-Hong Dong 2 *, Yong-Wei Chen 2 , Xian-Qiang Wang 2 , Chong-Hui Li 2 , Jian Wang 2 , Guo-Qiang Wang 2 , Hai-Lin Li 2 , Xue-Dong Wang 2 Matsumoto et al, 2002;Saita et al, 2002). Subsequent studies revealed that Gal-9, similar to other galectins, modulated a variety of biological functions, such as cell aggregation and adhesion, apoptosis of tumor cells, and others (Asakura et al, 2002;Hirashima et al, 2004).…”
Section: Introductionmentioning
confidence: 99%